High Treatment Success Rates Among HIV-Infected Multidrug-Resistant Tuberculosis Patients After Expansion of Antiretroviral Therapy in Botswana, 2006–2013. (1st January 2017) - Shin, Sanghyuk S.; Modongo, Chawangwa; Boyd, Rosanna; Caiphus, Cynthia; Kuate, Lesego; Kgwaadira, Botshelo; Zetola, Nicola M.
Abstract : Background: Few studies have examined multidrug-resistant (MDR) tuberculosis (TB) treatment outcomes among HIV-infected persons after widespread expansion of antiretroviral therapy (ART). We describe MDR-TB treatment outcomes among HIV-infected and HIV-uninfected patients in Botswana after ART expansion. Methods: We retrospectively reviewed data from patients who started MDR-TB therapy in Botswana during 2006–2013. Multivariable regression models were used to compare treatment outcomes between HIV-infected and HIV-uninfected patients. Results: We included 588 MDR-TB patients in the analysis, of whom, 47 (8.0%) and 9 (1.5%) were diagnosed with pre-extensively drug-resistant (XDR)-TB and XDR-TB, respectively. Of the 408 (69.4%) HIV-infected patients, 352 (86.0%) were on ART or started ART during treatment, and median baseline CD4 + T-cell count was 234 cells/mm 3 . Treatment success rates were 79.4% and 73.0% among HIV-uninfected and HIV-infected patients, respectively ( P = 0.121). HIV-infected patients with CD4 + T-cell count <100 cells/mm 3 were more likely to die during treatment compared with HIV-uninfected patients (adjusted risk ratio = 1.890; 95% CI: 1.098 to 3.254). Conclusions: High rates of treatment success were achieved with programmatic management of MDR-TB and HIV in Botswana after widespread expansion of ART. However, a 2-fold increase in mortality was observed among HIV-infected persons with baseline CD4 + <100 cells/mm 3 compared with HIV-uninfected persons.